2019
DOI: 10.1002/smtd.201800512
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Iron Oxide‐Based Nanoarchitectures for Biomedical, Energy Storage, and Environmental Applications

Abstract: Iron oxide nanoarchitectures with distinct morphologies from 1D to 3D have been developed using various wet chemical methods. They have been employed for a wide range of applications, including energy storage, biomedical, and environmental applications. The functional properties of iron oxide nanoarchitectures depend on the size, shape, composition, magnetic properties, and surface modification. To overcome the limitations of pure iron oxide nanostructures, hybridizations with various inorganic materials (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(46 citation statements)
references
References 296 publications
(541 reference statements)
1
45
0
Order By: Relevance
“…Presently, electric vehicle technology advances require high energy density from Li‐ion batteries for commercial realization. Ni‐rich materials have attracted much attention as potential candidates due to their high reversible capacity, discharge working voltage, and relatively low costs .…”
Section: Introductionmentioning
confidence: 99%
“…Presently, electric vehicle technology advances require high energy density from Li‐ion batteries for commercial realization. Ni‐rich materials have attracted much attention as potential candidates due to their high reversible capacity, discharge working voltage, and relatively low costs .…”
Section: Introductionmentioning
confidence: 99%
“…Scientic evidence reported that the loading of various chemotherapeutic drugs in the nanomaterial has been conserved, and sometimes potentiated the activity. 24 On the one hand, Fe 3 O 4 treatment alone did not show any promising cytotoxicity at higher concentrations, indicating little effect on the cell viability ( Fig. S1B †).…”
Section: Qn and Fa-fe-sba15qn Induced Cytotoxicity In Hct 116 Cellsmentioning
confidence: 94%
“…Typically, the shape of nanoparticles can be classified through the related dimensionality ranges from zero‐dimensional (0‐D) to three‐dimensional (3D) simply. [ 112 ] Unlike 0‐D or 1‐D nanostructures, 3D magnetic nanostructures are mainly fabricated as clusters or assembled from units. Directional attachment during synthesis can controllably increase the magnetization of magnetic nanostructures without disturbing their superparamagnetic property.…”
Section: Property Optimization Of Fmionsmentioning
confidence: 99%